2022
DOI: 10.1111/apa.16572
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte proliferation favours viral clearance in young children with chronic hepatitis B virus infection

Abstract: Hepatitis B virus (HBV) infection is a global health problem. [1][2][3] Vertical transmission of HBV from hepatitis B surface antigen (HBsAg)-positive mothers to their neonates is the most common cause of HBV infection worldwide. [4][5][6] Despite passive-active immunoprophylaxis using hepatitis B vaccination with or without hepatitis B immunoglobulin, up to 8%-10% of newborns still acquire HBV infection. 7 Managing these children with HBV infection is of paramount importance, which has a direct and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In our study, FHIT was a high‐frequency integrated gene among infant patients, but it has rarely been reported as one of the main target human genes in adult patients with chronic hepatitis B. FHIT is a tumor suppressor gene with roles in cell proliferation and apoptosis 23,24 . In our recently published study, we found that hepatocyte proliferation favored HBV clearance in young children with chronic HBV infection 25 . Whether and how the integration of HBV DNA into FHIT affects hepatocyte proliferation or hepatitis B prognosis deserves further study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our study, FHIT was a high‐frequency integrated gene among infant patients, but it has rarely been reported as one of the main target human genes in adult patients with chronic hepatitis B. FHIT is a tumor suppressor gene with roles in cell proliferation and apoptosis 23,24 . In our recently published study, we found that hepatocyte proliferation favored HBV clearance in young children with chronic HBV infection 25 . Whether and how the integration of HBV DNA into FHIT affects hepatocyte proliferation or hepatitis B prognosis deserves further study.…”
Section: Discussionmentioning
confidence: 62%
“…23,24 In our recently published study, we found that hepatocyte proliferation favored HBV clearance in young children with chronic HBV infection. 25 Whether F I G U R E 5 Fragile histidine triad (FHIT) gene is the high-frequency integrated site at the intragenic region among infant patients.…”
Section: Discussionmentioning
confidence: 99%